A Potential Antibody-Drug Conjugate Targeting Human LIV1 for the Treatment of Triple-Negative Breast Cancer - Wei Zhang; Hong Liu; Wei-Liang Zhuang; Yuan Li; Li-Ping Xie; You-Jia Hu (Georg Thieme Verlag KG, 2023)
Triple-negative breast cancer (TNBC), which accounts for 15 to 20% of incidents of breast cancer, is the only breast cancer subtype that lacks targeted treatments. It was reported in the literature that LIV1 was highly expressed in TNBC and other solid tumors. This makes LIV1 a potential target for the treatment of TNBC. This study aimed to develop an anti-LIV1 antibody for the treatment of TNBC. In this study, a novel anti-LIV1 antibody Ab1120 was developed and conjugated with monomethyl auristatin E (MMAE) to obtain the antibody-drug conjugate, Ab1120-vcMMAE. The Cell Counting Kit-8 method was used to assess the killing effect of the antibody-drug conjugate on cell lines MDA-MB−231 (high LIV1 expression of breast cancer cell line), MDA-MB-468 (low LIV1 expression of breast cell line), and 293C18 (LIV1-negative human embryonic kidney cell). The antitumor effect of Ab1120-vcMMAE on an MDA-MB-231 xenograft model was determined by evaluating the tumor volume and body weight after its treatment. In vitro analysis showed that Ab1120-vcMMAE is a potent inhibitor against the proliferation of a LIV1 overexpression cell line. The in vivo results demonstrated its antitumor activity in the cell-derived xenograft breast tumor mouse model. The results of this study suggest that Ab1120-vcMMAE may be used as a new therapeutic drug for patients with LIV1 high-expression breast cancer.